AstroSat observations of the first Galactic ULX pulsar Swift J0243.6+6124. Issue 1 (21st October 2020) - Beri, Aru; Naik, Sachindra; Singh, Kulinder Pal; Jaisawal, Gaurava K; Bhattacharyya, Sudip; Charles, Philip; Ho, Wynn C G; Maitra, Chandreyee; Bhattacharya, Dipankar; Dewangan, Gulab C; Middleton, Matthew; Altamirano, Diego; et al.
ABSTRACT: Swift J0243.6+6124, the first Galactic ultraluminous X-ray pulsar, was observed during its 2017–2018 outburst with AstroSat at both sub- and super-Eddington levels of accretion with X-ray luminosities of LX ∼ 7 × 10 37 and 6 × 10 38 erg s −1, respectively. Our broad-band timing and spectral observations show that X-ray pulsations at 9.85 s have been detected up to 150 keV when the source was accreting at the super-Eddington level. The pulse profiles are a strong function of both energy and source luminosity, showing a double-peaked profile with pulse fraction increasing from ∼10 per cent at 1.65 keV to 40–80 per cent at 70 keV . The continuum X-ray spectra are well modelled with a high-energy cut-off power law (Γ ∼ 0.6–0.7) and one or two blackbody components with temperatures of ∼0.35 and 1.2 keV, depending on the accretion level. No iron line emission is observed at sub-Eddington level, while a broad emission feature at around 6.9 keV is observed at the super-Eddington level, along with a blackbody radius (121\!-\!142 km ) that indicates the presence of optically thick outflows.